Identification of the ACTB p.Ser348Leu de novo variant in individuals with syndromic neonatal diabetes - Ahmed, Suhel; Lewis, Victoria; Russ-Silsby, James; Wakeling, Matthew N.; Thunander, Maria; Vivanco, Maritza; Caswell, Richard; Hattersley, Andrew T.; Bowman, Pamela; Patel, Kashyap; Flanagan, Sarah E.; De Franco, Elisa (EBioMedicine, 2026)
Background: Identifying novel genetic causes of diabetes in the first 6 months of life (neonatal diabetes) can highlight genes and pathways essential for pancreatic beta-cell development and function in humans. Our aim was to uncover genetic aetiologies of neonatal diabetes. Methods: We performed genome sequencing in 38 probands diagnosed with neonatal diabetes without an identified genetic cause, and their unaffected parents. Genes with de novo coding variants in ≥2 probands were followed up. Replication was performed in a separate cohort of 288 genetically unresolved individuals diagnosed with neonatal diabetes. Findings: The de novo ACTB (p.Ser348Leu) variant was identified in two unrelated individuals. Both had diabetes onset soon after birth (1 and 8 days), low birthweight (−3.22SD and −3.98SD), and extra-pancreatic features (hearing loss and developmental delay in one; intestinal atresia in the other). The same ACTB (p.Ser348Leu) variant was reported in seven individuals in the literature; one individual had confirmed neonatal diabetes and a further two had hyperglycaemia. Extra-pancreatic features were similar to our probands (hearing loss in 3/7; neurodevelopmental features in 4/7; gastrointestinal atresia in 6/7). In total, 5/9 individuals with the ACTB (p.Ser348Leu) variant had neonatal diabetes or hyperglycaemia. None of the 96 cases with other ACTB pathogenic variants in the Human Gene Mutation Database had diabetes. Interpretation: The identification of 3 individuals (two in this report and one from the literature) with neonatal diabetes and a de novo ACTB p.(Ser348Leu) variant supports ACTB as a previously unrecognised neonatal diabetes aetiological gene, most likely through a variant-specific mechanism. Funding: Diabetes UK; EFSD/NNF; NIHR, Wellcome Trust.
Keywords: ACTB; Beta-actin; Genome sequencing; Neonatal diabetes